KONTRIBUSI LAYANAN SUPERVISI, KEPEMIMPINAN KEPALA SEKOLAH, DAN FASILITAS PEMBELAJARAN TERHADAP KINERJA GURU PENDIDIKAN JASMANI SMPN SE-KOTA CIMAHI - Mimin Karmini (Jurnal Pendidikan Jasmani Indonesia, 2009)
This research was grounded on the principle problems related to the low performance on the teaching physical education. Teachers performance itself is influenced by such factors as supervision service, principal leardership, and the availability of adequate learning facilities. With this support, teachers performance could be expected to gradually increase. In connection with this central issue, the authors try to identify specifically factors that contribute towards middle school PE teachers which will be the variable of the research. Theoritically, to improve PE teachers performance needs various efforts. The influential variables on the teachers performance are supervision service, principal leardership, and the availability of adequate learning facilities. This research was a descriptive research which means an inverstigation telling, analyzing, dan classifiying data collected using survey, interview, questionaire, or test. A number of 21 mixed sex PE teachers participarted in the research. They were choosen using a purposive sampling technique. It concludes that supervision service had 73,45% of the contribution, principal leadership had 31,36% of the contribution, and facilitities had 33,29% of contribution. This means that variables that have been the factors provide contribution to PE teachers performance. That is why, it needs institutional efforts from elementary schools in the Cimahi City by providing information to principals to work more optimally. Kata kunci: layanan supervisi, kepemimpinan kepala sekolah, fasilitas pembelajaran, dan kinerja guru